Low Dose of Apelin-36 Attenuates ER Stress-Associated Apoptosis in Rats with Ischemic Stroke - Qiu, Jian; Wang, Xin; Wu, Fei; Wan, Lei; Cheng, Baohua; Wu, Yili; Bai, Bo (Frontiers in Neurology, 2017)
Cerebral ischemia/reperfusion (I/R) injury-induced cellular apoptosis contributes to neuronal death in ischemic stroke, while endoplasmic reticulum stress (ERS) and subsequently triggered unfolded protein response (UPR) are the major mechanisms of cerebral I/R injury-induced apoptosis. A number of studies indicated that apelin-13 protects neurons from I/R injury-induced apoptosis. Apelin-36, the longest isoform of apelin, has stronger affinity to apelin receptor than apelin-13 does. However, the role of apelin-36 in ischemic stroke is less studied. In addition, preventive administration of apelin was applied in most studies, which could not precisely reflect its therapeutic potential in ischemic stroke. Here we first reported that low dose of apelin-36, other than apelin-13, administrated after ischemic stroke significantly reduced infarct volume in rats. Moreover, apelin-36 attenuated cerebral I/R injury-induced apoptosis and caspase-3 activation. Furthermore, apelin-36 suppressed I/R injury-induced CHOP and GRP78 elevation, indicating that apelin-36 inhibited ERS/UPR activation. Our study first demonstrated that post-stroke administration of low-dose apelin-36 could attenuate cerebral I/R injury-induced infarct and apoptosis, which is associated with the inhibition of cerebral I/R injury-induced ERS/UPR activation. Our data support the therapeutic potential of apelin-36 in ischemic stroke although further investigation is needed.